Joining Ti-47Al-2Cr-2Nb with a Ti/(Cu,Ni)/Ti clad-laminated braze alloy - Guedes, A. (2003)
The joining of Ti-47Al-2Cr-2Nb using Ti-15Cu-15Ni (wt.%) as braze alloy was investigated. Experiments were conducted at 980 and 1000ºC for 10 min. The microstructure and the chemical composition of the interfaces were studied by scanning electron microscopy (SEM) and by energy dispersive X-ray spectroscopy (EDS), respectively. For both processing conditions the reaction between the gamma-TiAl alloy and the braze alloy produced layered interfaces, which are essentially composed of apha2-Ti3Al and of Ti-Ni-Cu-Al and Ti-Ni-Cu intermetallic compounds. Microhardness tests showed that all reaction layers are harder than either the gamma or the (alpha2 + gamma) lamellar grains of the intermetallic alloy.